Non-coding RNAs as Biomarkers for Colorectal Cancer Screening and Early Detection - Slaby, Ondrej (Advances in experimental medicine and biology, 2016)
Early detection of colorectal cancer (CRC) is the key for prevention and the ability to impact long-term survival of CRC patients. Current CRC screening modalities are inadequate for global application because of low sensitivity and specificity in case of conventional stool-based screening tests, and high costs and a low participation compliance in colonoscopy. An accurate stool- or blood-based screening test with use of innovative biomarkers is an appealing alternative as it is non-invasive and poses minimal risk to patients. It is easy to perform, can be repeated at shorter intervals, and therefore would likely lead to a much higher compliance rates. Non-coding RNAs (ncRNAs) have recently gained attention because of their involvement in different biological processes, such as proliferation, differentiation, migration, angiogenesis and apoptosis. An increasing number of studies have demonstrated that mutations or abnormal expression of ncRNAs are closely associated with various cancers, including CRC. The discovery that ncRNAs (mainly microRNAs) are stable in stool and in blood plasma and serum presents the opportunity to develop novel strategies taking advantage of circulating ncRNAs as early diagnostic biomarkers of CRC. This chapter is a comprehensive examination of aberrant ncRNAs expression levels in tumor tissue, stool and blood of CRC patients and a summary of the current findings on ncRNAs, including microRNAs, small nucleolar RNAs, small nuclear RNAs, Piwi-interacting RNAs, circular RNAs and long ncRNAs in regards to their potential usage for screening or early detection of CRC.
Keywords: kolorektální nádory; feces; Sensitivity and Specificity; Plasma; Colorectal Neoplasms; sérum; adenom; pacientův souhlas se zdravotní péčí; Humans; Feces; nekódující RNA; lidé; Patient Acceptance of Health Care; krevní plazma; Gene Expression Regulation, Neoplastic; časná detekce nádoru; Serum; adenokarcinom; senzitivita a specificita; regulace genové exprese u nádorů; polypy tlustého střeva; Biomarkers, Tumor; Adenocarcinoma; Early Detection of Cancer; Adenoma; nádorové biomarkery; Colonic Polyps; RNA, Untranslated